POLA PENANAMAN TOLERANSI MELALUI INTERAKSI SOSIAL BERBASIS MULTIKULTURAL: Patterns Of Tolerance Cultivation Through Multicultural-Based Social Interaction - Pasmah Chandra; Debby Sulistia (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2020)
The case of intolerance in the educational environment has recently become increasingly unsettling. This problem threatens the integrity of the Unitary State of the Republic of Indonesia (NKRI). For that, we need a unique approach or pattern to preventing the development of intolerance in the educational environment. Tolerance education must be strengthened, especially in the school environment. Tolerance education is practiced in the learning process and outside the classroom to become a school culture. Tolerance education must be broad, covering the internal tolerance of Muslims and between religious communities. This study aimed to determine the pattern of cultivating patience through multicultural-based social interactions among Muslim and non-Muslim students. This type of research is field research (field research) with a qualitative approach with Muslim and non-Muslim student respondents in Elementary School (SD) N 13 Argamakmur. Based on the results of the study, it is known that the application of the value of tolerance carried out by teachers in schools, mainly Islamic religious education teachers, in the learning process through an attitude that can understand the differences by placing in the position of each student, can generate mutual respect between one another. The habituation process pressed directly and intensively can create positive habits towards students. Students can view each other positively even though they have a religion, ethnicity, race, ethnicity, and customs that are different from others.